Adolescent Delinquency and Adulthood Economic Disadvantage and Job Benefits: Results From a Longitudinal Sample of Males and Females - Turgumbayev, Marlen (International journal of offender therapy and comparative criminology, 2024)
There is a long history of examining the connection between crime and delinquency and economic well-being and employment quality. Despite this vast literature, there still remains unanswered questions surrounding these associations, including whether the timing of adolescent delinquency is associated with adulthood economic disadvantage and job quality, whether different types of adolescent delinquency maintain differential associations with measures of economic disadvantage and employment quality in adulthood, and whether any associations between delinquency and economics/employment are invariant between males and females. The current study sought to address these issues by exploring the associations between adolescent involvement in nonviolent and violent delinquency (measured at two times in adolescence) and adulthood economic disadvantage and job quality. To do so, data drawn from the National Longitudinal Study of Adolescent to Adult Health were analyzed. The results revealed consistently null associations between the measures of adolescent delinquency and economic disadvantage and job quality for males. For females, however, the results were consistently significant, indicating that females who self-reported greater involvement in delinquency were more likely to be economically disadvantaged as adults and to have lower quality jobs. These results indicate that the associations between delinquency and economic disadvantage and job benefits differs between males and females, with females, in comparison with males, paying a significantly greater toll for engaging in acts of violent and nonviolent delinquency.